EFFECTIVENESS OF HYPNOTHERAPY IN INSOMNIA PATIENTS: SYSTEMATIC LITERATURE REVIEW - Dyah Pradnyaparamita Duarsa; Cokorda Bagus Jaya Lesmana; Ariana, Putu Agus; I Made Ady Wirawan (jfpublisher, 2022)
Introduction. Insomnia is a sleep disorder that is often a complaint in the elderly which ischaracterized by difficulty sleeping and maintaining sleep. There are various recommendedtherapies for the management of insomnia. One of the therapies used was hypnotherapywhich aimed to find out, compare and analyze hypnotherapy as an intervention inInsomnia. Method. This study used a systematic review design, following guidelinesdescribed by the Preferred Reporting Items for Systematic Review and Meta-Analysis(PRISMA). The library source search was conducted online using the Google Scholar,Pubmed, and Science Direct databases. The keywords used are